THE EFFECT OF THE PURCHASE DECISION PROCESS ON THE SELECTION OF SPORTSWEAR - Varel Ridho Ramantika; Muhammad Sholahuddin (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines how interactive content, advertising personalization, and user experience affect purchase decisions in Indonesia’s sportswear e-commerce market, with consumer trust positioned as a mediating variable. The study responds to the limited empirical evidence regarding the simultaneous influence of multiple digital marketing factors on consumer behavior in online shopping contexts. This study employed a quantitative explanatory approach involving 200 respondents who had made online purchases of sportswear products within the last six months. Data collection relied on an online survey distributed with five-point Likert-scale measurements, whereas hypothesis evaluation employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS software. Findings indicate that interactive content alongside personalized advertising significantly and positively drives purchasing decisions. Meanwhile, user experience fails to show a direct statistically meaningful impact on purchase decisions. The results further reveal that consumer trust is unable to significantly mediate the effect of the independent variables on purchasing decisions.. These findings suggest that consumers tend to respond more strongly to personalized and engaging digital marketing strategies than to platform usability and trust-related considerations when making online sportswear purchases.